Melatonin and Male Reproductive Health: Relevance of Darkness and Antioxidant Properties - Rocha, C.S.; Rato, L.; Martins, A.D.; Alves, M.G.; Oliveira, P.F. (Current Molecular Medicine, 2015)
The pineal hormone melatonin controls several physiological functions that reach far beyond the regulation of the circadian rhythm. Moreover, it can be produced in extra-pineal organs such as reproductive organs. The role of melatonin in the mammalian seasonal and circadian rhythm is well known. Nevertheless, its overall effect in male reproductive physiology remains largely unknown. Melatonin is a very powerful endogenous antioxidant that can also be exogenously taken safely. Interestingly, its antioxidant properties have been consistently reported to improve the male reproductive dysfunctions associated with pathological conditions and also with the exposure to toxicants. Nevertheless, the exact molecular mechanisms by which melatonin exerts its action in the male reproductive system remain a matter of debate. Herein, we propose to present an up-to-date overview of the melatonin effects in the male reproductive health and debate future directions to disclose possible sites of melatonin action in male reproductive system. We will discuss not only the role of melatonin during darkness and sleep but also the importance of the antioxidant properties of this hormone to male fertility. Since melatonin readily crosses the physiological barriers, such as the blood-testis barrier, and has a very low toxicity, it appears as an excellent candidate in the prevention and/or treatment of the multiple male reproductive dysfunctions associated with various pathologies.
Keywords: sperm